Alzheimer’s disease: Development of a sensitive label-free electrochemical immunosensor for detection of amyloid beta peptide - Carneiro, Pedro (2017)
In this work, a highly sensitive label-free immunosensor for detection of the main biomarker of Alzheimer’s disease (AD), amyloid beta 1–42 (Aβ (1–42)), is presented. A gold electrode was modified with a mercaptopropionic acid (MPA) self-assembled monolayer, electrodeposited gold nanoparticles (AuNPs) and a monoclonal antibody mAb DE2B4 to recognize Aβ; all the relevant experimental variables were optimized. Antibodies were functionalized through chemical modification (thiolation) to promote the antibody immobilization on the AuNPs surface with proper orientation which enabled the direct detection of Aβ(1–42). Scanning electron microscopy, square-wave voltammetry and electrochemical impedance spectroscopy were used to characterize the construction of the biosensor. Using the proposed immunosensor, Aβ(1–42) was specifically detected within the linear range of 10–1000 pg mL−1 with a 5.2 pg mL−1 and 17.4 pg mL−1 detection and quantification limit, respectively; recovery values for the tested spiking levels ranged from 90.3 to 93.6%. The immunosensor enables rapid, accurate, precise, reproducible and highly sensitive detection (14.6%reduction mL pg−1) of Aβ with low-cost and opens the possibilities for diagnostic ex vivo applications and research-based in vivo studies.